INTERNET AS AN EXTREMIST TOOL USED BY YOUTH ASSOSIATIONS - I Yu Abalov (RUDN Journal of Public Administration, 2015)
The article is devoted to the problem of using the Internet as a tool of unification of efforts and positions of extremist organizations. The author emphisizes the fact that the Internet and social networks allow to create new, previously unknown mechanisms of public mobilization, in particular to organize a large number of people using flashmob. The article presents a brief overview of the quality characteristics of the sites of criminals, attracting the attention of people, and ways of organizing people into extremist groups in social networks. The author concludes that the shortage of legal forms of influence on the socio-political situation creates preconditions for self-organization of young people online and in reality. To overcome this situation, the author identifies a number of factors that determine peculiarities of extremism development in the youth environment.